Educación LGB+. El derecho fundamental a educación básica contra la discriminación por orientación sexual - Gonzales Otoya, Bruno Doig (2019)
The present paper justifies the existence of a fundamental right to an education that addresses and seeks to eradicate discrimination based on sexual orientation. To this end, the justification relies on the text of the Constitution, judicial precedents, and moral reasons. Specifically, the hypothesis is based on the right to equality and the right to education, widely recognized by the constitutional practice. Thereafter, the means of implementation for the said right are presented. Finally, the argument is confronted with the critics related to the power of the parents to guide the education of their children, which is based on the principles of pluralism and state neutrality.